Texting and sexting among Jamaican youths: Educational, social, psychological and legal impacts [PowerPoint presentation] - Daley-Morris, Paula; Berry, Camille (My University, 2013)
This presentation explores the impact that widespread ownership of cell phones by Jamaicans has on the behaviour of youth age 15-25. This qualitative study examined the practice of texting and sexting by the young in Jamaica, through focus group interviews, the testimonial of one teen, detailed analysis of Jamaica's constitution, byelaws and acts, as well as available cyber-crimes data. The findings revealed that texting is the most popular vehicle of communication among Jamaicans, and its popularity has given rise to the practice of sexting. Sexting continues to play an important role in youth dating culture, but in many cases it is also the means through which sexual indiscretions, i.e. e-blasting, bullying and cyber-crimes occur. Extreme cases of sexting have resulted in social as well as psychological damage, which have altered the lives of some Jamaicans. In most cases these victims are left defenseless as the laws of the Jamaica are yet to catch-up with ills of telecommunication
Paper presented at the Biennial Conference of The University of the West Indies Schools of Education, 23-25 April, 2013, St. Augustine, Trinidad and Tobago
Keywords: Secondary school students; Youth; Text messaging; SMS; Sexual behaviour; Educational problems; Social effects; Psychological effects; Legal aspects; Conference papers; Jamaica